Enriched numerical procedures for bolt reinforced fully saturated fractured porous media. (December 2020) - Gujjala, Yashwanth Kumar; Deb, Debasis
Abstract: Stability analysis of underground structures made in fractured porous continua requires knowledge of rock deformation and pore pressure. Often, reinforcements in terms of rock bolts are installed to enhance the stability and hence the interaction between rock mass and bolt shank becomes inevitable. Extended Finite Element Method (XFEM) has been applied to handle the pre-existing joint planes and rock bolts. Porous media is simulated using Biot's consolidation theory, whereas fluid flow through fracture is achieved via Cubic law. This paper presents a comprehensive numerical formulation of fractured porous rock media with reinforcement and fluid flow. Apart from solving a benchmark problem, stability of a reinforced tunnel in the vicinity of a joint is also presented using the proposed numerical procedure.